2022
DOI: 10.1200/jco.22.01207
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Patients With Ovarian Cancer Experiencing the Highest Benefit From Bevacizumab in the First-Line Setting on the Basis of Their Tumor-Intrinsic Chemosensitivity (KELIM): The GOG-0218 Validation Study

Abstract: PURPOSE In patients with high-grade ovarian cancer, predictors of bevacizumab efficacy in first-line setting are needed. In the ICON-7 trial, a poor tumor intrinsic chemosensitivity (defined by unfavorable modeled cancer antigen-125 [CA-125] ELIMination rate constant K [KELIM] score) was a predictive biomarker. Only the patients with high-risk disease (suboptimally resected stage III, or stage IV) exhibiting unfavorable KELIM score < 1.0 had overall survival (OS) benefit from bevacizumab (median: 29.7 v 20.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
4
20
0
Order By: Relevance
“…In a subgroup analysis of GOG-0218 31 , in which cases were divided by mutation status in homologous recombination repair-related genes, there was no significant difference in the trends (Figure 5E). The results were also similar in another subgroup analysis of GOG-0218 stratified by chemosensitivity status as determined by changes in blood CA125 levels 32 (Figure 5F).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In a subgroup analysis of GOG-0218 31 , in which cases were divided by mutation status in homologous recombination repair-related genes, there was no significant difference in the trends (Figure 5E). The results were also similar in another subgroup analysis of GOG-0218 stratified by chemosensitivity status as determined by changes in blood CA125 levels 32 (Figure 5F).…”
Section: Resultssupporting
confidence: 80%
“…Given that bevacizumab is effective for only about a year and has a rebound effect after its discontinuation, it is likely that the benefit of bevacizumab, including improved survival and quality of life, will only be seen in patients with short survival. Our findings may explain the results of previous studies that bevacizumab did not prolong overall survival (OS) in the ICON7 and GOG-0218 overall cohorts 46, 47 but did prolong OS in chemotherapy-refractory, high-risk patients 32, 48 .…”
Section: Discussionsupporting
confidence: 80%
“…Both ICON-7 and GOG-0218 validation studies showed an association between unfavorable KELIM score and benefit from bevacizumab for progression-free survival and overall survival. 68 In clinical trials with PARP inhibitors, a favorable KELIM score may be associated with higher PARP inhibitor efficacy. In the VELIA trial, veliparib combined with carboplatinpaclitaxel, followed by maintenance veliparib was associated with improved progression-free survival compared with chemotherapy alone.…”
Section: Biomarker-based and Translational Endpointsmentioning
confidence: 99%
“…Our findings may explain the results of previous studies that bevacizumab did not prolong overall survival in the ICON7 and GOG-0218 overall cohorts 37,38 but prolonged overall survival in chemotherapy-refractory, high-risk patients. 22,39 The absence of rebound effect in the studies of recurrent ovarian cancer (eFigure 5A-C in Supplement 1) seems to be attributed to the protocol that did not stop bevacizumab until disease progression. [23][24][25] A similar result was observed in the MITO-16B trial 26 in which patients received bevacizumab in the first-line treatment and again in recurrent disease (eFigure 5D in Supplement 1).…”
Section: Relative Riskmentioning
confidence: 99%